Author Correction: Comprehensive aptamer-based screening identifies a spectrum of urinary biomarkers of lupus nephritis across ethnicities - Samantha Stanley (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.